Development Of Health Technology Methodologies: An Indepth Study Based On Medical Devices - Yuqing , Dong; Binti Tajudin, Noraisyah; Nizamudin Inamdar, Mohammad (Cuestiones de Fisioterapia, 2023)
Finding methods by which current medical technology may enhance healthcare delivery by enabling treatment that is more targeted, accurate, and efficient is the major objective of the project. It is imperative that the researcher incorporate these technologies into the researcher’s operational and clinical processes if the researcher want to achieve improved outcomes for everyone in the healthcare system. The reason for this initiative is that, over the course of the next several years, the advancement of medical technology will continue to proceed at a tremendous speed. This study investigates a wide range of medical equipment, including diagnostic, monitoring, and therapeutic tools, to name just a few of the many distinct categories of medical apparatus. To evaluate the influence that various kinds of medical equipment have on the development and enhancement of health technology practices, the purpose of this study is to investigate the repercussions of the many effects that are created by these practices. It is important to consider how the technology may enhance patient care and clinical decision-making, as well as how simple it is to use and how effectively it handles the integration of data. It is the objective of this research project to assess medical devices based on three criteria: the degree to which they are able to expedite operations, the frequency with which they eliminate medical errors, and the degree to which they properly prescribe medicines. To do this, the researcher have relied on methods that are part of quantitative research. Within the scope of the researcher’s investigation, the researcher used both qualitative and quantitative methods to accomplish this goal. They argue for improved interoperability, real-time monitoring, and individualised treatment; they also stress the strategic use of medical equipment. This approach is a significant advance in the field of health technology techniques